The population ecology of male gametophytes: The link between pollination and seed production - Harder, Lawrence D. (2016)
The fate of male gametophytes after pollen reaches stigmas links pollination to ovule fertilisation, governing subsequent siring success and seed production. Although male gametophyte performance primarily involves cellular processes, an ecological analogy may expose insights into the nature and implications of male gametophyte success. We elaborate this analogy theoretically and present empirical examples that illustrate associated insights. Specifically, we consider pollen loads on stigmas as localised populations subject to density-independent mortality and density-dependent processes as they traverse complex stylar environments. Different combinations of the timing of pollen-tube access to limiting stylar resources (simultaneous or sequential), the tube distribution among resources (repulsed or random) and the timing of density-independent mortality relative to competition (before or after) create signature relations of mean pollen-tube success and its variation among pistils to pollen receipt. Using novel nonlinear regression analyses (two-moment regression), we illustrate contrasting relations for two species, demonstrating that variety in these relations is a feature of reproductive diversity among angiosperms, rather than merely a theoretical curiosity. Thus, the details of male gametophyte ecology should shape sporophyte reproductive success and hence the dynamics and structure of angiosperm populations.